The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3348/kjr.2011.12.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemotherapy and Pulsed High-Intensity Focused Ultrasound Therapy for the Treatment of Unresectable Pancreatic Cancer: Initial Experiences

Abstract: ObjectiveThis study was performed to evaluate the potential clinical value of concurrent chemotherapy and pulsed high intensity focused ultrasound (HIFU) therapy (CCHT), as well as the safety of pulsed HIFU, for the treatment of unresectable pancreatic cancer.Materials and MethodsTwelve patients were treated with HIFU from October 2008 to May 2010, and three of them underwent CCHT as the main treatment (the CCHT group). The overall survival (OS), the time to tumor progression (TTP), the complications and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…Similar effects have been observed by others [114, 130132]. In all cases, patients received systemic chemotherapy concurrently with FUS treatments, but chemotherapy had been ineffective prior to initiation of FUS therapy.…”
Section: Introductionsupporting
confidence: 81%
“…Similar effects have been observed by others [114, 130132]. In all cases, patients received systemic chemotherapy concurrently with FUS treatments, but chemotherapy had been ineffective prior to initiation of FUS therapy.…”
Section: Introductionsupporting
confidence: 81%
“…Recently, several papers have reported the successful use of HIFU for pancreas tumors [3][4][5][6]. Anatomical locations of these types of lesions preclude the use of minimally-invasive procedures such as radiofrequency, microwaves, cryotherapy, ethanol injection, or embolisation procedures but allow the treatment with HIFU.…”
Section: Discussionmentioning
confidence: 99%
“…Initial trials of HIFU ablation of unresectable pancreatic cancer during chemotherapy showed higher survival and longer time to tumor progression than chemotherapy alone (19.5 vs. 10.3 months and 11.6 vs. 4.4 months respectively). No major complications were reported (Lee et al 2011). Our study suggests that such enhanced drug delivery depends on the HIFU parameters used.…”
Section: Discussionmentioning
confidence: 99%